Prospects of carbon fiber composites applications in hydraulic supports - Guo, Haiwei; Zhou, Miaomiao; Li, Pengfei; Lv, Meng; Zhang, Yufang (Frontiers in Materials, 2022)
This paper briefly analyzes the current development of lightweight design and applications for hydraulic support in the coal mines. Specifically, the comparative investigations of lightweight design demonstrate the potential application for carbon fiber reinforced composites (CFRP) in the production and manufacturing process of hydraulic support. After analyzing the major industrial applications of CFRP in the three main parts, hydraulic structure, cylinder and special frames, it demonstrated the feasibility of the potential CFRP exploitations in the future research of hydraulic support for coal mining sites.